Effects of the different plant design parameters on the performance improvement of the concentrated solar plant in low direct normal irradiance region. Issue 6 (3rd May 2023) - Bhattacharjee, Rahul; Bhattacharjee, Subhadeep
ABSTRACT: Critical analyses such as the combined effect of the design point DNI, SM, and TES on the plant performance in terms of capacity factor, plant generation, levelized cost of energy (LCOE), and plant efficiency have been done to find the better combination for low sunbelt region. From the study, it is found that the right combination of SM, design point DNI and TES, and the optimal mirror sizing gives very promising plant work tries to find the effect of different combinations of the design point DNI, solar multiple (SM), and thermal energy storage (TES) on the thermo-economic performance of the STPP for the low sunbelt region. Different critical analyses such as the combined effect of the design point DNI, SM, and TES on the plant performance in terms of capacity factor, plant generation, levelized cost of energy (LCOE), and plant efficiency have been done to find the better combination for low sunbelt region. From the study, it is found that the right combination of SM, design point DNI and TES, and the optimal mirror sizing gives very promising plant output, subjected to the low DNI condition. From the study, the best combination of SM, design point DNI and TES are found to be 2, 600 W/m 2, and 9.4 hrs, respectively. With this combination, the highest capacity factor is 41.6% and the minimum LCOE is 0.1684 $/kWh for the mirror size of 6 × 5 m 2 (width × height) and the plant efficiency is 18.45%. With the best combination of SM, design point DNI and TES the highest plant efficiency is found to be 18.64% with the mirror dimension of 8 × 5 m 2, where the LCOE and capacity factor are found to be 0.1691 $/kWh, and 41%, respectively.